2016
DOI: 10.1371/journal.pgen.1006263
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Functions of miR156-Regulated SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPL) Genes in Arabidopsis thaliana

Abstract: Correct developmental timing is essential for plant fitness and reproductive success. Two important transitions in shoot development—the juvenile-to-adult vegetative transition and the vegetative-to-reproductive transition—are mediated by a group of genes targeted by miR156, SQUAMOSA PROMOTER BINDING PROTEIN (SBP) genes. To determine the developmental functions of these genes in Arabidopsis thaliana, we characterized their expression patterns, and their gain-of-function and loss-of-function phenotypes. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
554
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(583 citation statements)
references
References 96 publications
(148 reference statements)
24
554
1
4
Order By: Relevance
“…In agreement with levels of miR156 being high in young seedlings and gradually decreasing with plant age Xu et al, 2016aXu et al, , 2016b, we found that in mature shoots, juvenile leaves had significantly higher levels of miR156 compared to miR156 levels in transition and adult leaves (Fig. 5B).…”
Section: Temporal Changes In Mir156 and Spl Expression Identify Splssupporting
confidence: 86%
See 1 more Smart Citation
“…In agreement with levels of miR156 being high in young seedlings and gradually decreasing with plant age Xu et al, 2016aXu et al, , 2016b, we found that in mature shoots, juvenile leaves had significantly higher levels of miR156 compared to miR156 levels in transition and adult leaves (Fig. 5B).…”
Section: Temporal Changes In Mir156 and Spl Expression Identify Splssupporting
confidence: 86%
“…SPL9-group genes have also been shown to function in flowering time Wu et al, 2009), with SPL15 playing a more important role than other SPL genes under long-d conditions (Xu et al, 2016a(Xu et al, , 2016b. In addition, other components of the flowering pathways including FLOWERING LOCUS C (FLC) and FLOWERING LOCUS T, also have effects on VPC and leaf morphology, and these effects can be either flowering-dependent or -independent (Willman and Poethig, 2011).…”
Section: Temporal Changes In Mir156 and Spl Expression Identify Splsmentioning
confidence: 99%
“…Different signaling pathways may therefore exist (Matsoukas, 2014b;Hyun et al, 2017). Nevertheless, the juvenile-toadult phase transition and attainment of floral competence are both controlled by decreased expression of miR156 and increased expression of its targets, the group of SBP/SPL transcription factor genes (Wu and Poethig, 2006;Wu et al, 2009;Xu et al, 2016; Fig. 1).…”
Section: Juvenile-to-adult Phase Transitionmentioning
confidence: 99%
“…While there is overlap in SPL function, different members of the SPL transcription factor family also have specific developmental functions in vegetative phase change and the floral transition (Xu et al, 2016).…”
Section: Floral Transitionmentioning
confidence: 99%
“…An important regulator of maintaining the juvenile vegetative phase, by repression of SQUAMOSA PROMOTOR BINDING PROTEIN LIKE (SPL) genes, is micro RNA 156 (miR156). Only repression of this miRNA in the shoot, initiated by a leaf derived signal, will result in the vegetative phase change by activation of its targets SPL9, SPL13 and SPL15 Yang et al, 2010;Xu et al, 2016). The miR156/ SPL module is conserved and this has been functionally confirmed in e.g.…”
Section: A B C Dmentioning
confidence: 83%